DESIGN AND SYNTHESIS OF 4-SUBSTITUTED QUINAZOLINE DERIVATIVES FOR THEIR ANTICONVULSANT AND CNS DEPRESSANT ACTIVITIES - Dash, Biswajit; Dash, Suvakanta; Laloo, Damiki (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The present work is designed to synthesise some isomeric new series of Quinazoline-4-one/4-thione derivatives, based on the pharmacophoric model of central nervous system (CNS) activity by structural modifications retaining the essential structural features for the activity and evaluated for their anticonvulsant and CNS depressant properties. Methods: A series of 7-chloro-3-[substituted (amino/phenylamino)]-2-phenyl quinazolin-4 (3H)-one/thione derivatives and 1-(7-chloro-4-oxo/-2-phenylquinazoline-3 (4H-yl)) substituted urea derivatives were prepared. The reaction scheme proceeds through the intermediate 7-chloro-2-phenyl-4H-benzo[d] [1, 3] oxazin-4-one. The structures of the newly synthesised compounds were characterized from infrared (IR), 1H nuclear magnetic resonance (NMR) and mass spectra (m/z) and elemental analysis. The anti-convulsant and CNS depressant activity were investigated by maximum electroshock (MES) seizure test and porsolt's behavioural despair test (forced swimming) respectively. The rota-rod test was performed to assess any probable changes in motor coordination induced by the test compounds. Results: The physicochemical and spectroscopic data clearly confirmed the synthesis of quinazoline derivatives with a common skeleton. The synthesised compounds were evaluated for their anticonvulsant and CNS depressant properties. Among them, six compounds (IIc, IIg, IIj, IIIc, IIIg, IIIj) exhibited a good activity profile in CNS depressant activity. Five compounds (IIc, IIg, IIj, IIIg, IIIh) showed protection against MES-induced seizures. Conclusion: The Quinazoline derivatives obtained from this research work indicates that the methyl/methoxy group in phenyl ring, amine and thiourea substitution at 3rd position of quinazoline derivatives are essential for CNS depressant activity as well as anticonvulsant activity. Compounds IIc, IIg, IIj, IIIc, IIIg, IIIj, and IIIh were found to be a potent compound which may be effective as a potential source for the development of CNS depressant and anti-convulsant drugs with lesser side effects